Systolic blood pressure at age 40 and 30-year stroke risk in men and women - Trygve Berge; Arnljot Tveit; Marius Myrstad; Inger Ariansen; Magnus Nakrem Lyngbakken; Håkon Ihle-Hansen; Thea Vigen; Helge Røsjø; Bente Thommessen; Ole Morten Rønning; Marte Meyer Walle-Hansen; Hege Ihle-Hansen; et al. (Open Heart)
Background American and European guidelines define hypertension differently and are sex agnostic. Our aim was to assess the impact of different hypertension thresholds at the age of 40 on 30-year stroke risk and to examine sex differences.Methods We included 2608 stroke-free individuals from the Akershus Cardiac Examination 1950 Study, a Norwegian regional study conducted in 2012–2015 of the 1950 birth cohort, who had previously participated in the Age 40 Program, a nationwide health examination study conducted in 1990–1993. We categorised participants by systolic blood pressure (SBP) at age 40 (<120 mm Hg (reference), 120–129 mm Hg, 130–139 mm Hg and ≥140 mm Hg) and compared stroke risk using Cox proportional hazard regressions adjusted for age, sex, smoking, cholesterol, physical activity, obesity and education. Fatal and non-fatal strokes were obtained from the Norwegian Cardiovascular Disease Registry from 1 January 2012 to 31 December 2020, in addition to self-reported strokes.Results The mean age was 40.1±0.3 years (50.4% women) and mean SBP was 128.3±13.5 mm Hg (mean±SD). Stroke occurred in 115 (4.4%) individuals (32 (28%) women and 83 (72%) men) during 29.4±2.9 years of follow-up. SBP between 130 and 139 mm Hg was not associated with stroke (adjusted HR 1.71, 95% CI 0.87 to 3.36) while SBP ≥140 mm Hg was associated with increased stroke risk (adjusted HR 3.11, 95% CI 1.62 to 6.00). The adjusted HR of stroke was 4.32 (95% CI 1.66 to 11.26) for women and 2.66 (95% CI 1.03 to 6.89) for men, with non-significant sex interactions.Conclusions SBP ≥140 mm Hg was significantly associated with 30-year stroke risk in both sexes. A small subgroup of women had SBP ≥140 mm Hg and systolic hypertension was a strong risk factor for stroke in these women.Trial registration number NCT01555411.